Ankylosing Spondylitis Disease Activity Score (ASDAS): defining cut-off values for disease activity states and improvement scores. Issue 1 (10th November 2010) - Machado, Pedro; Landewé, Robert; Lie, Elisabeth; Kvien, Tore K; Braun, Jürgen; Baker, Daniel; van der Heijde, Désirée; ,
Abstract : Background: The Ankylosing Spondylitis Disease Activity Score (ASDAS) is a new composite index to assess disease activity in ankylosing spondylitis (AS). It fulfils important aspects of truth, feasibility and discrimination. Criteria for disease activity states and improvement scores are important for use in clinical practice, observational studies and clinical trials and so far have not been developed for the ASDAS. Objective: To determine clinically relevant cut-off values for disease activity states and improvement scores using the ASDAS. Methods: For the selection of cut-offs data from the Norwegian disease modifying antirheumatic drug (NOR-DMARD) registry, a cohort of patients with AS starting conventional or biological DMARDs, were used. Receiver operating characteristic analysis against several external criteria was performed and several approaches to determine the optimal cut-offs used. The final choice was made on clinical and statistical grounds, after debate and voting by Assessment of SpondyloArthritis international Society members. Crossvalidation was performed in NOR-DMARD and in Ankylosing Spondylitis Study for the Evaluation of Recombinant Infliximab Therapy, a database of patients with AS participating in a randomised placebo-controlled trial with a tumour necrosis factor blocker. Results: Four disease activity states were chosen by consensus: inactive disease, moderate, high and very high disease activity. The three cut-offs selected to separate these states were: 1.3, 2.1 and 3.5 units. Selected cut-offs for improvement were: change ≥1.1 units for clinically important improvement and change ≥2.0 units for major improvement. Results of the crossvalidation strongly supported the cut-offs. Conclusions: Cut-off values for disease activity states and improvement using the ASDAS have been developed. They proved to have external validity and a good performance compared to existing criteria.